The Effect of Learning Community in Improving Students' Ability in Solve Math Problems in Class V - Zunarni, Anita; Sakina, Balik Shalikhatus; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Students' skills in solving problems in mathematics have an impact on learning outcomes. Mathematical problems are closely related to students' daily lives. These problems can be resolved through discussion and collaboration. A learning community is a learning model that facilitates problem-solving in a learning community. In society, students play an active role by changing knowledge in problem-solving. The purpose of this research is to know the effect of mathematical problem-solving ability in class with a Learning Community. The method used is a quasi-experimental design with a nonequivalent control group design. The results of this study indicate an increase in the mathematical problem-solving ability of the experimental class with a percentage of N-Gain in the experimental class of 65. 84% are categorized as quite effective. The experimental class and the control class showed differences in mathematical problem-solving abilities which were indicated by a significance level of < 0.05, this indicates that there is an influence of the learning community on increasing mathematical problem-solving abilities. The results of the research in the experimental class can be concluded that the learning community has an influence on improving students' ability to solve mathematical problems.